Neonatal congenital mesoblastic nephroma that caused respiratory oncologic emergency early after birth: a case report - Hirotaka Kato; Yasuyuki Mitani; Taro Goda; Hiroki Yamaue (BMC, 2022)
Abstract Background Congenital mesoblastic nephromas mainly present as asymptomatic abdominal masses, but some present hematuria, hypertension or hypercalcemia. Neonatal dyspnea in an early-birth neonate due to rapid tumor growth is reported here for the first time. Case presentation A renal tumor and polyhydramnios were detected by ultrasonography of a male fetus at 32 weeks and 3 days of gestation. The mother had abdominal distension due to the polyhydramnios and signs of imminent premature birth. Amniocentesis was performed and the signs of imminent preterm birth subsided, but growth of the renal tumor was noted as a potential cause of respiratory dysfunction. Cesarean section was performed at 36 weeks and 2 days of gestation. His birthweight was 2638 g and his 1 and 5 min APGAR scores were 2 and 4 points, respectively. There was no spontaneous breathing at birth and he had remarkable abdominal distention. He underwent cardiopulmonary resuscitation. After circulation stabilized, emergency surgery was performed because of progressive hypoxemia and respiratory acidosis. Laparotomy revealed a huge tumor arising from the right kidney and right nephrectomy was performed. Histopathological examination led to diagnosis of congenital mesoblastic nephroma. The respiratory condition and circulatory dynamics stabilized after the pressure on the thorax from the tumor was relieved by surgery. The postoperative course was uneventful. No recurrence or complications have been observed in the 36 months since the surgery. Conclusions Congenital mesoblastic nephroma can rapidly increase in size from the fetal period and may cause respiratory oncologic emergency, although there is relatively good prognosis.